-3(y-2)=6-3y

Simple and best practice solution for -3(y-2)=6-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(y-2)=6-3y equation:


Simplifying
-3(y + -2) = 6 + -3y

Reorder the terms:
-3(-2 + y) = 6 + -3y
(-2 * -3 + y * -3) = 6 + -3y
(6 + -3y) = 6 + -3y

Add '-6' to each side of the equation.
6 + -6 + -3y = 6 + -6 + -3y

Combine like terms: 6 + -6 = 0
0 + -3y = 6 + -6 + -3y
-3y = 6 + -6 + -3y

Combine like terms: 6 + -6 = 0
-3y = 0 + -3y
-3y = -3y

Add '3y' to each side of the equation.
-3y + 3y = -3y + 3y

Combine like terms: -3y + 3y = 0
0 = -3y + 3y

Combine like terms: -3y + 3y = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 9x-6x+4=-20 | | Y=4cos(6x) | | 56+28x= | | 16-4b=2(8-2b) | | 6*6-(7+5)= | | 3x^2+5x=11 | | -9=27-11p-13b | | 17=-2w-5 | | wz+5xy=8v | | 5-8abs(-2n)=-75 | | 7(q-3)=7q-3 | | -2+3p=-29 | | 5x-(9x+2)=-10 | | -6h-14+5h=h+14 | | 6(10+20)=180 | | 16a-10=3a+17 | | x+x-3+x+8+x-5=360 | | 7x-3x=10.2 | | 5x-(3x-6)=22 | | 7x+1=126 | | 6x^3=200 | | 8(2)+n=31 | | 1.4x+13.32=2.35x+21.92 | | (x-9)/7=3x | | 3-4(2x+7)=23 | | 10b-8=12b-10 | | 4(4/2+4)= | | 87+98+90+85=x | | -4(5x+2)=52 | | 8x+4(-4x+7)=34-8x | | x-9/7=3x | | x=43+86+51 |

Equations solver categories